Vigor for In Vitro Culture Traits in S. melongena × S. aethiopicum Hybrids with Potential as Rootstocks for Eggplant - Irene Calvo-Asensio; Jaime Prohens; Carmina Gisbert (The Scientific World Journal)
Hybrids of Solanum melongena and S. aethiopicum are of interest as rootstocks of eggplant, as they are highly vigorous and can incorporate resistance to several diseases. However, hybridization between both species is difficult. Therefore, protocols for in vitro culture are of great interest for their micropropagation and biotechnological breeding. We assessed the organogenesis response from leaf explants in four interspecific hybrids and in their parents testing two organogenic media: SIM-A, containing 6-benzylaminopurine and kinetin, and SIM-B, which contains thidiazuron. A higher regeneration capacity in the hybrids compared to their parents was observed. Whereas in interspecific hybrids and in one accession of S. melongena similar regeneration rates were observed for SIM-A and SIM-B, higher regeneration was found in the rest of genotypes when thidiazuron was used. Rooting ability in the interspecific hybrids was lower in in vitro micropropagated plants (35–60%) than in plants regenerated from explants (100%). The addition of indolbutiric acid (1 mg L−1) induced roots in nonrooted genotypes. In summary, we have adjusted in vitro culture conditions for regenerating and rooting S. melongena × S. aethiopicum hybrids. We have also demonstrated that these hybrids are heterotic for regeneration, which may be of interest for basic science studies.